Investigation of thermal asphalt mastic and mixture to repair potholes. (20th March 2019) - Li, Jiusu; Liu, Jianfang; Zhang, Wenbo; Liu, Guanlan; Dai, Lingchun
Graphical abstract: Highlights: Lack of thermal conductivity results in inefficient heat transfer in traditional pothole patching materials. Thermal asphalt mortar and thermal asphalt concrete were evaluated. Conductivity of thermal asphalt mix was four times that of the traditional asphalt mix. Abstract: Asphalt pavements maintenance is a critical infrastructure issue. This paper reports on a high thermal conductivity asphalt pavement mastic and mixture. Thermal asphalt mortar (ThAM) produced with asphalt, silicon-carbide (SiC) powder in the presence, and absence, of styrene-butadiene styrene (SBS), was evaluated. Optimal SBS and SiC proportions were determined by optimization and the balance of viscosity, ductility, and temperature stability. The results indicated that SBS and SiC optimum contents were 5% and 10%, respectively. The corresponding penetration (25 °C), ductility (5 °C), and softening point were 44 dmm, 380 mm and 78 °C, respectively. Heat absorption rates for both thermal asphalt (ThA) and traditional asphalt (TrA) were tested and compared. It showed that temperature differences up to 30 °C. Two types of thermal asphalt concrete (ThAC), blending with iron powder or not, were prepared. ThAC performance was systematically evaluated. The dynamic stability achieved 5872 times/mm, whereas the low temperature bending stiffness modulus was 5505 MPa, indicating both the rutting resistance and cracking resistance favorable. The most unfavorable load position was analyzed using a node tracking method, Bond strength was five times of the maximum shear stress. ThAC and TrA mix thermal conductivities were compared. ThAC thermal conductivity was 19.642 W/(m·K), which was four times that of the TrA mix.